Roesch, Genevieve (audio interview #3 of 3) - Roesch, Genevieve (b. 00/00/1907 - d. 2/24/1997); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the final of three interviews conducted with Genevieve Roesch in her daughter's home in Fullerton. At the time of the interview, work was being done on her own home in Tujunga. Initially self conscious, she gradually warmed up and seemed to enjoy the interview process, noting that it was making her think about things she hadn't thought of for years. She was surprised when the tape was turned off, commenting on how much she was talking.